Jenis-Jenis Bambu Dataran Tinggi di Sempadan Sungai Trengwilis Taman Nasional Gunung Rinjani Lombok - Fatmalasari, Dewi; Mulyaningsih, Tri Mulyaningsih; Aryanti, Evy (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2019)
Indonesia has 176 species and 24 genera of bamboos, around 11.5% of the total bamboo species in the world. In Lombok, there were found 6 genera, 15 species and 8 varieties. Bamboo has an important role on the river banks, it can prevent erosion of the river cliffs. The purpose of this study was to identify the species of highland bamboos, at the border of the Trengwilis river, Rinjani Mount National Park, Lombok. This research was conducted by descriptive explorative method, on July - April 2019. The Collecing data was used line sampling methode, with exploring the river border, 50 meters from the left and right edges of riverbed. Data collection in the field was carried out by recording 72 bamboo characters. The results were found eight species of bamboo which were included in five genera, e.g. Bambusa vulgaris Schard., Schizotachyum sp., Dendrocalamus sp. Dendrocalamus asper (Schult) Backer, Gigantochloa sp., Gigantochloa atter (Hassk.) Kurz., that were found at an attitude 623m-660m asl.; Gigantochloa apus (Schult.) Kurz. that grew as long as the Trengwilis riverbed at around atitude 623m-729m asl.; and Dinochloa sp. was found at an atitude 716m asl. Genus Dinochloa was a new record in West Nusa Tenggara Region.